KETERKAITAN ANTARA DUKUNGAN KELUARGA DENGAN HARGA DIRI PADA PASIEN ULKUS DIABETIK DI POLIKLINIK PENYAKIT DALAM RSUD Dr. MOEWARDI SURAKARTA - Fahrun Nur Rosyid; Dessy Kurniawati Ruslan (STIKES YPIB Majalengka, 2017)
Diabetic ulcers can affect the patient's psychological disruption that self-esteem,causing feelings of guilt or blame, aloof behavior or avoidance of social interaction thatcan have an impact on the healing process even worsen the prognosis. This study aimedto analyze the relationship between family support and self-esteem in patients withdiabetic ulcers.This study is a is a cross sectional study. The population in this study is a diabeticulcer patients who seek treatment at the Polyclinic Internal Medicine Hospital Dr.Moewardi Surakarta, the sample of 30 patients. The sampling technique used was quotasampling. This study uses a measuring instrument in the form of a questionnaire. Thevariables of this study is the family support and self-esteem. Data have been collected andwas later analyzed by using Spearman Rank Correlation.The results of this study were (1) the family support to patients with diabeticulcers are mostly good, (2) Price patient diabetic ulcer majority is moderate and (3) thereis a relationship between family support and self-esteem in patients with diabetic ulcers.The conclusion is that family support showed mostly good and a fraction less.While the self-esteem majority and minority were lacking, and the results of the analysisshowed no relationship between family support and self-esteem diabetic ulcer patients.Support their families can maintain and increase self-esteem.